Environmental influences on life history strategies in partially anadromous brown trout (Salmo trutta, Salmonidae). Issue 6 (9th August 2019) - Nevoux, Marie; Finstad, Bengt; Davidsen, Jan Grimsrud; Finlay, Ross; Josset, Quentin; Poole, Russell; Höjesjö, Johan; Aarestrup, Kim; Persson, Lo; Tolvanen, Oula; Jonsson, Bror
Abstract: This paper reviews the life history of brown trout and factors influencing decisions to migrate. Decisions that maximize fitness appear dependent on size at age. In partly anadromous populations, individuals that attain maturity at the parr stage typically become freshwater resident. For individual fish, the life history is not genetically fixed and can be modified by the previous growth history and energetic state in early life. This phenotypic plasticity may be influenced by epigenetic modifications of the genome. Thus, factors influencing survival and growth determine life‐history decisions. These are intra‐ and interspecific competition, feeding and shelter opportunities in freshwater and salt water, temperature in alternative habitats and flow conditions in running water. Male trout exhibit alternative mating strategies and can spawn as a subordinate sneaker or a dominant competitor. Females do not exhibit alternative mating behaviour. The relationship between growth, size and reproductive success differs between sexes in that females exhibit a higher tendency to migrate than males. Southern populations are sensitive to global warming. In addition, fisheries, aquaculture with increased spreading of salmon lice, introduction of new species, weirs and river regulation, poor water quality and coastal developments all threaten trout populations. The paper summarizes life‐history data from six populations across Europe and ends by presenting new research questions and directions for future research.